Realizing the Witch : Science, Cinema, and the Mastery of the Invisible. - Baxstrom, Richard (Forms of Living Ser., 2015)
Realizing the Witch follows the unfolding of Benjamin Christensen's visual narrative in his 1922 film, H#65533;xan (The Witch). Through a close reading of H#65533;xan, Baxstrom and Meyers examine the study of witchcraft from historical and anthropological perspectives, as well as the intersection of popular culture, artistic expression and scientific ideas.